DOES TAX AVOIDANCE SENSITIVE TO THE COVID-19 PANDEMIC? - Permata Ayu Widyasari; Divaldo Juselvec Yulfan; Maria Euginia Hastuti (Jurnal Bisnis dan Akuntansi, 2024)
This research was conducted to obtain empirical evidence related to changes in tax avoidance carried out by companies before and after the Covid-19 pandemic, from 2019 to 2022. This research examines it further using two tests, including a two-category difference test and the MANOVA test. This basic research is carried out using a quantitative approach with secondary data in financial reports. The objects used in this research were 366 non-financial companies. This research uses several substitute variables for tax avoidance: book tax difference, GAAP effective tax rate, current effective tax rate, cash tax rate, and effective tax rate differential. Based on different tests, BTD is more sensitive in capturing differences in tax avoidance due to different statutory rates in 2019. The MANOVA test found no differences in tax avoidance from before to after the pandemic in 2019, 2020, 2021 and 2022. This indicates that income declined during the pandemic, but the tax payout ratio remained unchanged. Therefore, the pandemic has not changed the level of tax avoidance practices in Indonesia.